Prosecuting poverty, criminalizing care - Bach, Wendy A. (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
At the height of the opiate epidemic, Tennessee lawmakers made it a crime for a pregnant woman to transmit narcotics to a fetus. They promised that charging new mothers with this crime would help them receive the treatment and support they often desperately need. In Prosecuting Poverty, Criminalizing Care, Wendy Bach describes the law's actual effect through meticulous examination of the cases of 120 women who were prosecuted for this crime. Drawing on quantitative and qualitative data, Bach demonstrates that both prosecuting 'fetal assault', and institutionalizing the all-too-common idea that criminalization is a road to care, lead at best to clinically dangerous and corrupt treatment, and at worst, and far more often, to an insidious smokescreen obscuring harsh punishment. Urgent, instructive, and humane, this retelling demands we stop criminalizing care and instead move towards robust and respectful systems that meet the real needs of families in poor communities.
Creating a crime to create care -- Framing and reframing -- Laying the ground -- Punishing poverty -- Deepening poverty and degrading justice -- The path in : from healthcare to child welfare to criminal systems -- Criminalization as a road to care and the price you pay -- Corrupting care -- A path forward.
Title from publisher's bibliographic system (viewed on 25 Aug 2022).
Keywords: Substance abuse in pregnancy -- Law and legislation -- Tennessee -- Criminal provisions; Pregnant women -- Legal status, laws, etc. -- Tennessee; Fetus -- Legal status, laws, etc. -- Tennessee